Imaging mechanism and degradation characteristic analysis of novel rotating synthetic aperture system - Zhi, Xiyang; Jiang, Shikai; Zhang, Lei; Wang, Dawei; Hu, Jianming; Gong, Jinnan (Optics and lasers in engineering, 2021)
•The imaging mechanism of the novel rotating synthetic aperture system is deduced.•The image degradation model of the rotating synthetic aperture system is presented.•The effects of factors causing image quality degradation are analyzed. The Rotating synthetic aperture (RSA) is one of the most promising novel imaging systems to meet the requirements of lightweight and high resolution for optical remote sensing satellites, especially in geostationary orbit. The point spread function (PSF) orientation relative to the observed scene, intentionally changes to measure all spatial frequency information available to a filled circular aperture having a diameter approximately equal to the length of the rectangular aperture. As with all precision optical systems, RSA is also subject to dynamic disturbances from the spacecraft/environment. If not accommodated properly in the measurement and synthesis process, the dynamic disturbances can result in significant image quality degradation. To quantify methods to reduce or eliminate the errors, we first analyze the on-orbit imaging mechanism of the RSA system theoretically and then represent the worst-case on-orbit imaging degradation characteristics.